Evaluation of the long-term compressive strength development of the sewage sludge ash/metakaolin–based geopolymer - Istuque, D. [UNESP]; Soriano, L.; Borrachero, M. V.; Payá, J.; Akasaki, J. L. [UNESP]; Melges, J. L.P. [UNESP]; Tashima, M. M. [UNESP] (Editorial CSIC, 2021)
This paper aimed to evaluate the long-term compressive strength development of the sewage sludge ash/metakaolin (SSA/MK)–based geopolymer. SSA/MK–based geopolymeric mortars and pastes were produced at 25ºC with different SSA contents (0 - 30 wt.%). Compressive strength tests were run within the 3-720 curing days range. A physicochemical characterisation (X-ray diffraction and scanning electron microscopy) was performed in geopolymeric pastes. All the geopolymeric mortars presented a compressive strength gain with curing time. The mortars with all the SSA evaluated contents (10, 20, 30 wt.%) developed a compressive strength over 40 MPa after 720 curing days at 25ºC. The maximum compressive strength of the mortars with SSA was approximately 61 MPa (10 wt.% of SSA), similarly to the reference mortar (100% MK-based geopolymer). The microstructure analyses showed that the SSA/MK–based geopolymer presented a dense microstructure with N-A-S-H gel formation.
Keywords: Alkali-activated cement; Compressive strength; Metakaolin; Mortar; Scanning electron microscopy